1993
DOI: 10.3109/08916939309043887
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Dependent Diabetes in the Nod Mouse Model I. Detection and Characterization of Autoantibody Bound to the Surface of Pancreatic Beta Cells Prior to Development of the insulitis Lesion in Prediabetic Nod Mice

Abstract: Type I, insulin-dependent diabetes (IDD) results from an autoimmune response against the insulin producing pancreatic beta cells. This autoimmune reaction involves both humoral and cell-mediated factors; nevertheless, the relative role of each remains unresolved. Furthermore, while adoptive transfer experiments have provided evidence for the role of T cells in beta cell destruction, the specific events which initiate leukocyte migration into the islets (insulitis) are unknown. Earlier studies indicated that NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…Accordingly, binding of IgM to beta cells has been described in vivo in very young NOD mice [10]. We showed here that NOD B1a-derived IgM binds to beta cells in vitro and that the expression of Nos2 is upregulated in islet cells in contact with NOD B1a-derived supernatant fraction, suggesting that IgM binding is involved in triggering the beta cell oxidative stress response.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Accordingly, binding of IgM to beta cells has been described in vivo in very young NOD mice [10]. We showed here that NOD B1a-derived IgM binds to beta cells in vitro and that the expression of Nos2 is upregulated in islet cells in contact with NOD B1a-derived supernatant fraction, suggesting that IgM binding is involved in triggering the beta cell oxidative stress response.…”
Section: Discussionmentioning
confidence: 56%
“…It has previously been shown that NOD mice, but not C57BL/6 nondiabetic control mice, have antibodies bound to beta cells before the development of insulitis. Interestingly, these antibodies are mainly of the IgM isotype [10] and thus are unlikely to originate in germinal centre reactions. Consistently, young NOD mice have a pronounced repertoire of IgM AAbs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, knowing that NOD mouse develop cell immune mediated diabetes, many of the experiments aim to picture the immunological status which is responsible for the onset of diabetes [37,38]. It is important to bear in mind that diabetes in NOD mice is not only the result of cell mediated immunity but also of humoral factors as GAD and IgM [39].…”
Section: Spontaneous Iddm Based On Animal Modelsmentioning
confidence: 99%
“…Additionally, sera collected from these animals contain auto‐antibodies that bind to β‐cells of both T1D‐prone and T1D‐resistant mice. Auto‐antibodies binding to pancreatic β‐cells in this strain are predominantly of the IgM isotype, 24 therefore an early humoral response may be involved in β‐cell targeting, the initiation of insulitis, and subsequent disease development. Natural auto‐antibodies bound to pancreatic islet antigens can trigger complement system–mediated inflammation, 25 which may contribute to the observed deregulation in the NOD mouse immune system and modulate T1D development.…”
Section: Natural Auto‐antibodies As Pancreatic Islet Injurersmentioning
confidence: 99%